Management of standing pig production information, decision making supported by soft methodologies - Ojeda Enríquez, Miguel (Scientia et Technica, 2018)
The transformation and progressive evolution of the pig sector, towards more complex, technified and larger systems, has caused that the management of the data of the dynamics of production being fundamental to achieve a high level of information, allowing an efficient decision-making and effective. This article presents an organizational study experience oriented to the design of a model for the management of information in pig production on foot for La Esperanza farm of Fusagasugá Colombia. The design was based on the interpretation of the system of human activities (productive system) through the soft systems methodology (MSB) and, in the identification of productive dynamics and decision making, through system dynamics (DS) with the software "Evolution 4.5". Finally, the model for the management of information guided the construction of a prototype of the information system, "UCPigModel", which serves the human pig production system.